Barriers of purchasing departments' involvement in marketing service procurement - Bals, Lydia; Hartmann, Evi; Ritter, Thomas (Industrial Marketing Management, 2009)
A considerable part of firms' marketing services are supplied by external providers, e.g. advertisement agencies, printing houses, trade fair exhibition builders. Although a large spend category, low involvement of purchasing departments prevails during the procurement decision process. This paper develops a conceptual model of purchasing departments' involvement in marketing service procurement along the dimensions “breadth along process” and “depth of integration”, thus contributing to the measurement of purchasing departments' involvement. Drawing on the findings of a case study, we further propose that the impact of purchasing departments' involvement on procurement success is moderated by procurement complexity, and the duration of the relationship between the purchasing and marketing employees. In addition, barriers to purchasing departments' involvement are conceptualized as lack of skills, lack of motivation, and lack of opportunity.
WiSo-Import:2015-03-26:1015
Keywords: Service; Purchasing; Procurement; Marketing; Involvement; Integration